1997
DOI: 10.1002/(sici)1097-4636(199710)37:1<137::aid-jbm17>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of fetal rat chondrocytes cultured on a bioactive glass-ceramic

Abstract: We examined the behavior of fetal rat chondrocytes cultured on a bioactive glass-ceramic containing apatite and wollastonite (A.W.G.C.). Biomaterial surface topography and profiles were evaluated by bidimensional profilometry and revealed a rough surface for the glass-ceramic compared to the plastic coverslips used as controls. Chondrocyte attachment was evaluated by measuring the number of attached cells after one day of culture and by morphological observations. Chondrocytes attached in great numbers to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…Furthermore, the distribution of vinculin in each group mirrored its F-actin distribution (Figure 4). The observed F-actin patterns of DIAS cells and chondrocytes in this study were similar to those reported for chondrocytes in monolayer (37,38). This implies that the 2 cell types have similar cell-matrix interactions.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, the distribution of vinculin in each group mirrored its F-actin distribution (Figure 4). The observed F-actin patterns of DIAS cells and chondrocytes in this study were similar to those reported for chondrocytes in monolayer (37,38). This implies that the 2 cell types have similar cell-matrix interactions.…”
Section: Discussionsupporting
confidence: 87%
“…3). The relationship between cell shape and differentiation has been widely described 13,14,52 , and we have previously shown that causing a change in cell shape by inhibiting RhoA activation enabled the reversion of the chondrogenic phenotype from a dedifferentiated state 53 . It was also recently reported that causing mesenchymal stem cells to conform to either a spread or spheroid shape differentially induced cell differentiation towards the osteogenic and adipogenic lineages, respectively, due to shape-driven influences in signaling pathways 54 .…”
Section: Discussionmentioning
confidence: 60%
“…Thus, it has been possible to study the responses of various cell types to numerous patterned surface features such as grooved structures, [14][15][16][17][18][19][20][21][22][31][32][33] nanometersized columns, 8,9 irregular roughness, 23,34,35 and regular arrays of micrometer-sized pillars. 9,24-27 Based on the results from the studies of surfaces with nanometer-sized pillars of random dimensions 8 and uniformly sized pillars in regular arrays, 9 our study was initiated to assess astroglial cell responses to pillars with well-defined heights (1 m), widths (0.5-2.0 m), and interpillar gaps (0.5-5.0 m).…”
Section: Discussionmentioning
confidence: 99%
“…Although most of these studies have not tried to mimic biological surfaces, more complex topographies have been shown to do so, as demonstrated by substrates patterned to direct fungi to targets. 13 Using microfabrication techniques, substrates have been patterned to study the responses of cell cultures to various topographical features such as grooves [14][15][16][17][18][19][20][21][22] , nonuniform nanometer-scale and/or roughened surfaces, 8,9,23 and arrays of pillars 9,24-27 and wells. 25,27 Surface topographies with regular as well as random geometries may be fabricated to study fundamental cell biology and control the surface properties that influence the integration of prosthetic devices into tissues.…”
Section: Introductionmentioning
confidence: 90%